Irisin and Myonectin Regulation in the Insulin Resistant Muscle: Implications to Adipose Tissue: Muscle Crosstalk - Gamas, Luís (2015)
Myokines are peptides produced and secreted by the skeletal muscle, with autocrine, paracrine, and endocrine actions. Many of them are overexpressed during physical exercise and appear to contribute to the benefits of exercise to metabolic homeostasis. Irisin, resulting from the cleavage of the membrane protein FNDC5, was shown to induce adipocyte browning, with increased lipid oxidation and thermogenesis. Myonectin was only recently discovered and initial studies revealed a role in fatty acid uptake and oxidation in adipose tissue and liver. However, the mechanisms of their regulation by exercise are not entirely established. Impaired secretion and action of myokines, such as irisin and myonectin, may have a role in the establishment of insulin resistance. On the other hand, several studies have shown that insulin resistance in the skeletal muscle may change myokines expression and secretion. This may have consequences on lipid and glucose metabolism in adipose tissue and lead to a vicious cycle between impaired myokines production and insulin resistance. This review summarizes the current knowledge about the influence of skeletal muscle insulin resistance on the secretion of irisin and myonectin, as well as its impact on adipose tissue metabolism.